Protein Arginine Methylation: An Emerging Modification in Cancer Immunity and Immunotherapy - Dai, Weijing; Zhang, Jianguo; Li, Siqi; He, Fajian; Liu, Qiao; Gong, Jun; Yang, Zetian; Gong, Yan; Tang, Fang; Wang, Zhihao; Xie, Conghua (Frontiers in Immunology, 2022)
In recent years, protein arginine methyltransferases (PRMTs) have emerged as new members of a gene expression regulator family in eukaryotes, and are associated with cancer pathogenesis and progression. Cancer immunotherapy has significantly improved cancer treatment in terms of overall survival and quality of life. Protein arginine methylation is an epigenetic modification function not only in transcription, RNA processing, and signal transduction cascades, but also in many cancer-immunity cycle processes. Arginine methylation is involved in the activation of anti-cancer immunity and the regulation of immunotherapy efficacy. In this review, we summarize the most up-to-date information on regulatory molecular mechanisms and different underlying arginine methylation signaling pathways in innate and adaptive immune responses during cancer. We also outline the potential of PRMT-inhibitors as effective combinatorial treatments with immunotherapy.